Model Integrated Border Management (IBM) dalam Pengelolaan Perbatasan Provinsi Kepulauan Riau untuk Meningkatkan Daya Saing Investasi untuk Mendukung Pertahanan Negara: Pengelolaan Perbatasan Provinsi Kepulauan Riau untuk Meningkatkan Daya Saing Investasi - Edy Saptono; Agus Sudarya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The position of the Riau Islands Province border area with Singapore is very strategic. Even though it has great potential to contribute to economic improvement, this position has not been utilized optimally, even though border areas are an attractive entry point for investors who intend to invest their capital. The aim of the research is to examine the Riau Islands Province Border Management Model based on Integrated Border Management (IBM) which refers to IBM parameters and competitiveness parameters as an effort to increase competitiveness in the investment sector. This research uses a qualitative analysis approach. The research results show that there are obstacles in the management of the Riau Islands-Singapore Province border area in the form of geographical, legal, management and security obstacles. Meanwhile, investment mechanisms and procedures in the border area of ​​Riau Islands Province with Singapore are not complicated and are regulated using a server. The Integrated Border Management (IBM) implementation model in managing the border between Riau Islands Province and Singapore to increase investment competitiveness uses the Single Window Model which is an integrated public service system.